Pengaruh Rekrutmen Pelatihan dan Lingkungan Kerja terhadap Kinerja Karyawan Pada Bagian Marketing pada PT Federal International Finance Surabaya Cabang Rajawali - Krido Hary Gunawan; Lailatul Fitria (Journal Economic Excellence Ibnu Sina, 2025)
This study aims to analyze the effect of recruitment, training, and work environment on employee performance at PT Federal International Finance Surabaya Rajawali Branch. This research employs a quantitative method with a survey approach. The sample consists of 41 respondents selected using a saturated sampling technique. Data were processed using SPSS version 29.0, including instrument tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing.The results reveal that simultaneously, recruitment, training, and work environment significantly influence employee performance. Partially, training has a significant impact on employee performance, whereas recruitment and work environment show no significant influence. These findings highlight that relevant training programs can enhance employee skills and productivity. Thus, training becomes a crucial factor for companies to focus on in improving employee performance.